La impunidad de las infracciones administrativas en el sector de las telecomunicaciones, por conflictos en la normativa legal que regula la potestad sancionadora de la administración. - Solano Ballesteros, Samantha Geraldine (2020)
The present investigation addresses the legal problem that lies in the impunity of administrative infractions in the telecommunications sector, due to inconsistencies in the legal regulations that govern the sanctioning power of the public administration. This is due to the incompatibility of articles 117, 118, 119, 120 and 121 of the Organic Telecommunications Law that typify infractions and sanctions within the telecommunications sector and article 245 of the Organic Administrative Code, which typifies the deadlines of prescription of administrative infractions using a catalog of infractions that is inconsistent with that provided for in the LOT, which makes current regulations inapplicable to offenses classified within this sector. This situation affects the principle of prescription that govern the exercise of the Ius Puniendi and legal security, therefore it can be affirmed that the inconsistencies in the legal regulations previously exposed, limit ARCOTEL to exercise the sanctioning power with which it is vested, what generates that infractions in the telecommunications sector go unpunished.